Correlation between platelet indices and preeclampsia with severe features - Fuady, Dzicky Rifqi; Yudatmo, Unggul; Ghazali, Muhammad Farid; Rosdiana, Dian; Arjadi, Fitranto (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Backgrounds: Pre-eclampsia is a pregnancy-related syndrome with a 2-8% prevalence worldwide. In Indonesia, its incidence was 128,273 (5.3%) cases that caused 30-40% of maternal deaths. In 2021, at Karawang General Public Hospital, there are 43% cases of pre-eclampsia with 3% of complication. The pathophysiology is related to the inflammatory and coagulation system that includes platelets. Thus, platelet indices as indicators for platelet changes could be potential laboratory markers for pre-eclampsia.Objective: To examine the relationship between the platelet indices and pre-eclampsia severe features at the Karawang General Public HospitalMethods: The six months cross-sectional study was conducted at the Karawang General Public Hospital for pre-eclampsia pregnant women with at least 28 weeks of gestational age. The pre-eclampsia criteria were blood pressure higher or equal to 140/90 mmHg and qualitative proteinuria dipstick +1. The subjects were divided into two groups: pre-eclampsia with severe features and without severe features. Severe features criteria were thrombocytopenia, impaired liver function, renal insufficiency, pulmonary edema, new onset headache, and visual disturbances. Pregnant women have their blood platelet indices checked in the form of platelet crit (PCT), mean platelet volume (MPV), platelet distribution width (PDW), and platelet large cell ratio (P-LCR). Data were analyzed with descriptive analysis (percentage), cut-off analysis, ROC curve, AUC analysis, bivariate Chi-square analysis, and multivariate logistic regression analysis.Results: There was a significant difference (p < 0.05) in the value of PCT, MPV, PDW, and P-LCR between pregnant pre-eclampsia women with severe features and pregnant pre-eclampsia women without severe features. P-LCR has the best sensitivity (52.9%) and specificity (98.9%).Conclusions: There was a significant change in the value of the platelet indices (PCT, MPV, PDW, P-LCR) in pregnant pre-eclampsia women with severe features at the Karawang General Public Hospital.